National Education Policy of India: A Comprehensive Roadmap for Transformative Education - Dr. S. Ramesh (Journal of Learning and Educational Policy, 2023)
The National Education Policy (NEP) of India, introduced in 2020, is a transformative policy that aims to revolutionize the country's education system. This article presents a comprehensive review of the literature on the NEP 2020, exploring its objectives, key features, implications, and challenges. The review highlights the policy's visionary approach in addressing critical issues such as access, quality, and holistic development in education. It emphasizes the potential of the NEP 2020 to reshape teaching practices, learning outcomes, and educational practices, while also identifying the challenges in its effective implementation. The study also discusses the role of technology, vocational education, and teacher empowerment in aligning with the policy's vision. The literature review underscores the significance of the NEP 2020 in fostering a knowledgedriven society and preparing India's youth for the challenges of the 21st century.